2003
DOI: 10.1007/s00436-003-1000-9
|View full text |Cite
|
Sign up to set email alerts
|

Angiostrongylus vasorum (Baillet, 1866) Kamensky, 1905: emergence of third-stage larvae from infected Biomphalaria glabrata snails

Abstract: Biomphalaria glabrata snails were experimentally infected with Angiostrongylus vasorum first-stage larvae and divided into four groups of 30 snails. To assess the shedding of third-stage larvae (L3), the snails were maintained under different stimuli: group 1 60 W light bulb for 24 h, group 2 37 degrees C water bath for 24 h, group 3 room temperature (23-25 degrees C) for 24 h, Group 4 room temperature (23-25 degrees C) for up to 15 days. After 24 h, a total of 512 A. vasorum L3, alive and active, were release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 11 publications
(12 reference statements)
6
39
0
Order By: Relevance
“…The tails of the 2 species appeared too similar to allow reliable accurate differentiation (Figs. 4 and 8 laboratory aquatic snails (Biomphalaria glabrata) but this is the first report in a terrestrial slug (Barcante et al 2003). Consistent with the findings of others excepting those studying the protostrongylids, the shedding level was relatively low (1 -3 % of the worm burden).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The tails of the 2 species appeared too similar to allow reliable accurate differentiation (Figs. 4 and 8 laboratory aquatic snails (Biomphalaria glabrata) but this is the first report in a terrestrial slug (Barcante et al 2003). Consistent with the findings of others excepting those studying the protostrongylids, the shedding level was relatively low (1 -3 % of the worm burden).…”
Section: Discussionsupporting
confidence: 88%
“…Excepting species infecting marine mammals or swine, the exposure route for most involve the ingestion of infective third-stage larvae (L3) contained in the tissues of a gastropod intermediate host or also in some species a paratenic host. (Barcante et al 2003, Boev 1975, Bonetti et al 1998, Giannelli et al 2015, Heyneman and Lim 1967, Jenkins et al 2006, Kralka and Samuel 1984, Kutz et al 2000, Monson and Post 1972, Ubelaker et al 1980. Recently gastropod L3 shedding has also been reported for a crenosomatid (Troglostrongylus brevior) (Giannelli et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The final host become infected by direct ingestion of an infected gastropod (or the paratenic host) or by food contaminated with slime from the gastropods (Rosen et al 1970;Bolt et al 1993; Barcante et al 2003). Upon ingestion, the L3 penetrate the gastrointestinal tract wall and migrate to the abdominal lymph nodes where they undergo two moults and develop into immature adult (L5; Rosen et al 1970;Guilhon and Cens 1973).…”
Section: Lifecyclementioning
confidence: 96%
“…Based on the in vitro experiments, more than 20 different species of terrestrial and aquatic slugs and snails have been found to be potential as intermediate host (Rosen et al 1970;Guilhon and Cens 1973;Sauerlander and Eckert 1974;Simpson and Neal 1982;Barcante et al 2003;Ferdushy et al 2010). Recent investigation on snails and slugs around Copenhagen area in Denmark demonstrated natural A. vasorum infection in nine different species of snails and slugs namely Arion ater, Arianta arbustorum, Arion lusitanicus, Arion subfuscus, Arion hortensis, Limax maximus, Cepaea nemoralis, Deroceras caruanae and Deroceras reticulatum, with A. ater and A. lusitanicus as the most heavily infected species than others (Ferdushy et al 2009;Koch and Willesen 2009).…”
Section: Host Rangementioning
confidence: 98%
“…In the common garden snail Cornu aspersum (syn Helix aspersa) for example, L3 have been detected after 10 days post-infection (Colella et al, 2016). Caniids acquire the infection via the ingestion of infected terrestrial snails or slugs (Stockdale & Hulland, 1970), however alternative routes of infection for the defi nitive and intermediate hosts have also been reported for metastrongyles infecting cats and dogs (Barçante et al, 2003;Giannelli et al, 2015). Canine crenosomosis is typically characterised by bronchitis with a dry, unproductive cough that can be elicited by tracheal palpation, with occasional gagging (Cobb & Fisher, 1992).…”
Section: Introductionmentioning
confidence: 99%